2024
DOI: 10.1037/pspi0000459
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal supports for basic psychological needs and their relations with motivation, well-being, and performance: A meta-analysis.

Gavin R. Slemp,
James G. Field,
Richard M. Ryan
et al.

Abstract: People's motivational processes, well-being, and performance are likely to be facilitated through the support of others. Self-determination theory argues that interpersonal supports for autonomy, competence, and relatedness are crucial to achieve these outcomes. In the present study, we provide a comprehensive examination of this formulation based on a meta-analytic database consisting of 4,561 effect sizes from 881 independent samples (N = 443,556). Our results indicate that supports for autonomy, competence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 155 publications
0
1
0
Order By: Relevance
“…When needs are met, they move in a positive direction towards self-improvement. Such requirements cannot be met spontaneously; instead, they must be realized with the assistance and support of the outside world [21][22][23], such as with parental support. It has been demonstrated that parental autonomy support can contribute to the positive development of individuals by satisfying basic psychological needs, which plays a mediating role [24,25].…”
Section: The Role Of Basic Psychological Needsmentioning
confidence: 99%
“…When needs are met, they move in a positive direction towards self-improvement. Such requirements cannot be met spontaneously; instead, they must be realized with the assistance and support of the outside world [21][22][23], such as with parental support. It has been demonstrated that parental autonomy support can contribute to the positive development of individuals by satisfying basic psychological needs, which plays a mediating role [24,25].…”
Section: The Role Of Basic Psychological Needsmentioning
confidence: 99%